A multicenter phase 1 study of solitomab (MT110, AMG 110), a bispecific EpCAM/CD3 T-cell engager (BiTE®) antibody construct, in patients with refractory solid tumors. (3rd August 2018) - Kebenko, Maxim; Goebeler, Marie-Elisabeth; Wolf, Martin; Hasenburg, Annette; Seggewiss-Bernhardt, Ruth; Ritter, Barbara; Rautenberg, Beate; Atanackovic, Djordje; Kratzer, Andrea; Rottman, James B.; Friedrich, Matthias; Vieser, Eva; et al.
ABSTRACT: We assessed the tolerability and antitumor activity of solitomab, a bispecific T-cell engager (BiTE®) antibody construct targeting epithelial cell adhesion molecule (EpCAM). Patients with relapsed/refractory solid tumors not amenable to standard therapy received solitomab as continuous IV infusion in a phase 1 dose-escalation study with six different dosing schedules. The primary endpoint was frequency and severity of adverse events (AEs). Secondary endpoints included pharmacokinetics, pharmacodynamics, immunogenicity, and antitumor activity. Sixty-five patients received solitomab at doses between 1 and 96 µg/day for ≥28 days. Fifteen patients had dose-limiting toxicities (DLTs): eight had transient abnormal liver parameters shortly after infusion start or dose escalation (grade 3, n = 4; grade 4, n = 4), and one had supraventricular tachycardia (grade 3); all events resolved with solitomab discontinuation. Six patients had a DLT of diarrhea: four events resolved (grade 3, n = 3; grade 4, n = 1), one (grade 3) was ongoing at the time of treatment-unrelated death, and one (grade 3) progressed to grade 5 after solitomab discontinuation. The maximum tolerated dose was 24 µg/day. Overall, 95% of patients had grade ≥3 treatment-related AEs, primarily diarrhea, elevated liver parameters, and elevated lipase. Solitomab half-life was 4.5 hours; serum levels plateaued within 24 hours. One unconfirmed partial response was observed. In this study of a BiTE® antibody construct targeting solid tumors, treatment of relapsed/refractory EpCAM-positive solid tumors with solitomab was associated with DLTs, including severe diarrhea and increased liver enzymes, which precluded dose escalation to potentially therapeutic levels.